Aplicativo KingDraw Chemical Structure como recurso digital didáctico en el proceso de enseñanza-aprendizaje de Química Orgánica con los estudiantes de sexto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología. - Sánchez Sánchez, Ángelo Elián (2024)
Mobile applications are digital resources that facilitate and improve the learning of Organic Chemistry. However, their use in university classrooms is scarce, leading the students to have little understanding and ignorance of the contents framed in the syllabus, which generates problems for the students. The present research's objective was to propose using KingDraw Chemical Structure as a digital didactic resource in teaching Organic Chemistry with the sixth-semester students of the Undergraduate Education of Experimental Chemical Sciences and Biology. The research methodology was non-experimental, bibliographical, field, and cross-sectional; inductive deductive methods and analysis-synthesis were used; a survey was applied to the 34 sixth-semester students. The data obtained showed that most respondents, 85%, fully agree that the application KingDraw is a digital didactic resource that complements the learning of Organic Chemistry, concluding that this mobile application stimulates, promotes, and enhances the learning of sixth semester students of the Degree in Pedagogy of Experimental Chemical Sciences and Biology. Therefore, it is recommended to use digital resources such as tools, software, and simulators to help the student structure organic compounds more easily and quickly, as well as their reaction mechanisms.